Impingement in total hip arthroplasty: A geometric model. (April 2022) - Pryce, Gregory M; Sabu, Bismaya; Al-Hajjar, Mazen; Wilcox, Ruth K; Thompson, Jonathan; Isaac, Graham H; Board, Tim; Williams, Sophie
Total Hip Arthroplasty (THA) is one of the most common and successful surgical interventions. The survivorship at 10 years for the most commonly used systems is over 95%. However, the incidence of revision is usually much higher in the 0–1 year time period following the intervention. The most common reason for revision in this early time period is dislocation and subluxation, which may be defined as complete or permanent, and partial or temporary loss of contact between the bearing surfaces respectively. This study comprises the development of a geometric model of bone and an in situ total hip replacement, to predict the occurrence and location of bone and component impingement for a wide range of acetabular cup positions and for a series of frequently practiced activities of daily living. The model developed predicts that anterior-superior component impingement is associated with activities that result in posterior dislocation. The incidence may be reduced by increased cup anteversion and inclination. Posterior-inferior component impingement is associated with anterior dislocation activities. Its incidence may be reduced by decreased cup anteversion and inclination. A component impingement-free range was identified, running from when the cup was positioned with 45° inclination and 25° anteversion to 70° inclination and 15°–20° anteversion.